2017
DOI: 10.1039/c7cp01737e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nanoparticle porosity via nanoimpacts and XPS: electro-oxidation of platinum nanoparticle aggregates

Abstract: The porosity of platinum nanoparticle aggregates (PtNPs) is investigated electrochemically via particle-electrode impacts and by XPS. The mean charge per oxidative transient is measured from nanoimpacts; XPS shows the formation of PtO and PtO2 in relative amounts defined by the electrode potential and an average oxidation state is deduced as a function of potential. The number of platinum atoms oxidised per PtNP is calculated and compared with two models: solid and porous spheres, within which there are two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous work looking at the response of individual mesoporous platinum nanoparticles have emphasized electrochemical accessibility of the internal interfaces toward the formation of surface oxides and have demonstrated the ability of HOR and HER to be studied on the single particle scale. This work studies the hydrogen oxidation reaction at individual mesoporous nanoparticles revealing how the nanoparticle structure contributes to the catalytic performance of the material. The study of single nanoparticle reactions has been partially hampered by colloidal stability in the presence of electrolytes. , However, since the 1980’s it has been recognized that use of a microelectrode enables redox reactions to be driven at an electrochemical interface in the absence of high electrolyte concentrations and without significant ohmic distortion. , This, as will be demonstrated, holds true at the nanoscale where due to the small currents involved (picoampere), redox reactions can be performed at individual nanoparticles in resistive media and importantly allow insight into the activity of the mesoscale nanoparticle structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work looking at the response of individual mesoporous platinum nanoparticles have emphasized electrochemical accessibility of the internal interfaces toward the formation of surface oxides and have demonstrated the ability of HOR and HER to be studied on the single particle scale. This work studies the hydrogen oxidation reaction at individual mesoporous nanoparticles revealing how the nanoparticle structure contributes to the catalytic performance of the material. The study of single nanoparticle reactions has been partially hampered by colloidal stability in the presence of electrolytes. , However, since the 1980’s it has been recognized that use of a microelectrode enables redox reactions to be driven at an electrochemical interface in the absence of high electrolyte concentrations and without significant ohmic distortion. , This, as will be demonstrated, holds true at the nanoscale where due to the small currents involved (picoampere), redox reactions can be performed at individual nanoparticles in resistive media and importantly allow insight into the activity of the mesoscale nanoparticle structure.…”
Section: Introductionmentioning
confidence: 99%
“…This value is still an order of magnitude larger than geometrically expected for a 15 nm radius sphere due to surface roughness and porosity (Supporting Information, Figure S1). Previous reports on particles from the same manufacturer have measured comparably large surface areas, attributed to the porosity of particles …”
Section: Resultsmentioning
confidence: 91%
“…In addition to sizing nanoparticles the nano-impact technique is able to simultaneously measure their concentration via the frequency of the observed impacts ( Stuart et al, 2012 ). Furthermore, the potentials at which the current spikes onset are clearly related to the chemical identity of the nanoparticles and recent work has shown that it is able to measure the states of agglomeration/aggregation of the particles ( Tschulik et al, 2014 ) and the porosity of the particles ( Jiao et al, 2017 ). Currently, the direct nano-impact studies on MOS mainly focus on the redox behavior of the MOS themselves Fe 3 O 4 ( Tschulik and Compton, 2014 ), Fe 2 O 3 ( Shimizu et al, 2016a ; Shimizu et al, 2016b ), ZnO ( Perera et al, 2015 ; Karunathilake et al, 2020 ; Ma et al, 2018 ) and CuO ( Zampardi et al, 2018 ) and the MOS surface-bound with electroactive species CeO 2 ( Karimi et al, 2019 ), TiO 2 ( Shimizu et al, 2017 ) and Al 2 O 3 ( Lin and Compton 2015 , 2017 ).…”
Section: Single Entity Electrochemistry Of Semiconducting Nanoparticlesmentioning
confidence: 99%
“…This powerful electrochemical technique has found much strength in giving insights into the fundamental study of nanoparticles: not only the basic particle characterization (e.g. sizing, concentration, chemical identity, agglomeration/aggregation state, porosity) ( Zhou et al, 2011 ; Stuart et al, 2012 ; Tschulik et al, 2014 ; Jiao et al, 2017 ; Li et al, 2019 ), but also in-depth understanding at single-particle levels for the mechanisms and dynamics of (photo) electrochemical processes of interest ( Xiao and Bard, 2007 ; Bard et al, 2010 ; Fernando et al, 2013 ; Li et al, 2016 ; Ma et al, 2018 ; Peng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%